Econometric Assessment of the Impact of Competitiveness on the Income of the Population in Azerbaijan - Yadulla Hasanli; Sardar Shabanov (Challenges and Issues of Modern Science)
The concept of global competitiveness index (GCI) was proposed in 2004. The GCI index is calculated by the World Economic Forum since 2007. The GCI is an aggregate indicator that includes more than 110 sub-indicators in 12 groups. According to the values of this indicator, the countries of the world are ranked in descending order.